Science and Poetry - Dalimir Hajko (Communications - Scientific letters of the University of Zilina, 2018)
Emotionality and rationality or differences and consensus regarding the basic units of the semantic plan of art and science. Relationship of the language and extra-linguistic area in scientific knowledge and poetry. Particularities of the poetic language and the language of science. Image and abstraction: a different ability of our spirit to reflect the world. The presence of metaphors in philosophy and natural sciences as a transcendence of common experience. Interactive understanding of metaphor and its pitfalls. Is metaphor usable in science and does it have a cognitive function?